2008
DOI: 10.1097/rct.0b013e31815074ce
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Multidetector Row Computed Tomography in Patient With Breast Cancer

Abstract: Although multidetector row computed tomography is not the primary method of evaluating breast cancer, it could be performed as an excellent alternative, especially in the presence of magnetic resonance contraindications. Moreover, computed tomography can still have an important role in evaluation of nodal status, thoracic invasion, and distant metastasis because of the large area covered in a single examination. Our experience together with literature indicates that multidetector row computed tomography is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…They can scan large anatomic areas several times faster than single-detector helical CT scanners (18, 26). Moreover, through thinner collimation, MDCT markedly improves the spatial and time resolution of images acquired to detect lesions (18, 26, 27). Therefore, there is potential usefulness of MDCT as a method for accurate evaluation of ALN status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can scan large anatomic areas several times faster than single-detector helical CT scanners (18, 26). Moreover, through thinner collimation, MDCT markedly improves the spatial and time resolution of images acquired to detect lesions (18, 26, 27). Therefore, there is potential usefulness of MDCT as a method for accurate evaluation of ALN status.…”
Section: Discussionmentioning
confidence: 99%
“…MDCT can obtain high-quality multiplanar images in fast scan time and allow three-dimensional reconstruction (17). Furthermore, preoperative MDCT can be performed with the patient in the supine position, which facilitates simultaneous localization of the lesion, and evaluation of its extent, as well as examination of the skin, chest wall, and regional lymph nodes, including both axillae, internal mammary, and supraclavicular chains (5, 8, 18). However, preoperative MDCT for evaluating ALN status in patients with breast cancer remains under-investigated (18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…In a different study, in which the detectability of the intraductal component of invasive ductal carcinomas at multidetector CT was compared with that at MR imaging in the same patients, investigators found that the lesion detectability at multidetector CT (61%) was inferior to that at MR imaging (75%) (23). In general, CT has lower sensitivity but higher specificity than MR imaging because the lesion appearance leads to overestimation of fibrocystic changes at MR imaging (25).…”
Section: Comparison Of Mr Imaging With Multidetector Ctmentioning
confidence: 99%
“…At present, it is not uncommon to use radiomics methods to predict the molecular subtypes of breast cancer, and many encouraging results have been obtained, most of which are based on the radiomics features of breast mammography, ultrasound, or MRI for model development and validation ( 9 11 ). CT also plays an important role in the clinical practice of breast cancer ( 12 ). Although most of the current guidelines do not recommend the utilization of chest CT as a routine examination for breast cancer diagnosis or early screening ( 13 , 14 ), in the actual diagnosis and treatment activities, because of the incidence of lung and bone metastasis in breast cancer patients, especially for patients with late clinical stage, chest CT is still one of the routine examinations in most patients.…”
Section: Introductionmentioning
confidence: 99%